The Impact of Employee Engagement and Organizational Commitment on Employee Performance - Endang Pitaloka; Fadhira Meirini Putri (Universitas Bunda Mulia, 2021)
PD SHANKAR PM is an import-export trade of the textile material company. During the pandemic, PD SHANKAR PM was one of the companies affected by Covid-19 due to a significant decrease in demand for fashion material. The pandemic also caused PD SHANKAR PM to impose a Work From Home (WFH) policy. This policy is new to all employees. With the challenge of surviving the Covid-19 crisis, companies need factors that drive employee performance. The purpose of this study was to determine work engagement, organizational commitment, and employee performance of PD SHANKAR PM during the work from home policy. Next, this study also aims to investigate the influence of work engagement and organizational commitment on employee performance of PD SHANKAR PM both simultaneously and partially. The method used in this research is a survey method by distributing questionnaires to 50 employees as respondents. The questionnaire data was then processed using descriptive statistical analysis techniques and multiple linear regression. The results showed that work engagement, organizational commitment, and employee performance of PD SHANKAR PM were in a good category. Work engagement and organizational commitment simultaneously have a significant effect on employee performance. Partially, work engagement has a significant effect on employee performance. Meanwhile, organizational commitment has no significant effect on employee performance. Although organizational commitment has no significant effect, organizational commitment and work engagement have a positive impact on employee performance